2007
DOI: 10.1074/jbc.m704485200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Redundancy between Two Caenorhabditis elegans Nucleotide Sugar Transporters with a Novel Transport Mechanism

Abstract: Transporters of nucleotide sugars regulate the availability of these substrates required for glycosylation reactions in the lumen of the Golgi apparatus and play an important role in the development of multicellular organisms. Caenorhabditis elegans has seven different sugars in its glycoconjugates, although 18 putative nucleotide sugar transporters are encoded in the genome. Among these, SQV-7, SRF-3, and CO3H5.2 exhibit partially overlapping substrate specificity and expression patterns. We now report eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
(43 reference statements)
1
18
2
Order By: Relevance
“…Seven other transporter genes (C53B4.6, F15B10.1, ZK370.7/ugtp-1, ZC250.3, C03H5.2, B0212.4, F54E7.1/pst-2) were tested by RNAi for altered sensitivity to M. nematophilum or other effects, using both rrf-3 and bus-12(br5) mutant backgrounds, but no abnormalities or bacterial resistances were observed. Caffaro et al (2007) have reported gonadal abnormalities associated with RNAi knockdown of C03H5.2, but only in a srf-3 mutant background.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven other transporter genes (C53B4.6, F15B10.1, ZK370.7/ugtp-1, ZC250.3, C03H5.2, B0212.4, F54E7.1/pst-2) were tested by RNAi for altered sensitivity to M. nematophilum or other effects, using both rrf-3 and bus-12(br5) mutant backgrounds, but no abnormalities or bacterial resistances were observed. Caffaro et al (2007) have reported gonadal abnormalities associated with RNAi knockdown of C03H5.2, but only in a srf-3 mutant background.…”
Section: Resultsmentioning
confidence: 99%
“…A precedent for such redundancy has been provided by Caffaro et al (2007), who found that RNAi knockdown of C03H5.2 (encoding a nucleotide sugar transporter related to SRF-3) had no obvious effect in wild-type or RNAi hypersensitive strains, but resulted in gonad abnormality in a srf-3 mutant background.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…cerevisiae cells transformed with empty vector p426GPD or p426GPD-TbNST1-4 were individually grown to an A 600 of ϳ2. Spheroplasts were prepared as previously described (39) using zymolase 100 T (Seikagaku America, Rockville, MD) and Golgi-enriched vesicles were obtained by fractionation of spheroplast suspension with successive centrifugation (40). Nucleotide sugar transport assays were carried out as previously described (39).…”
Section: Subcellular Fractionation and Nucleotide Sugar Transport Assaymentioning
confidence: 99%